Penguatan Civic Skills melalui Pendidikan Kewarganegaraan dalam Menumbuhkan Partisipasi Mahasiswa sebagai Warga Negara - Nurul Febrianti; Syurya Muhammad Nur; Silvia Ratna Juwita (Muhammadiyah University of Mataram, 2023)
This study aims to describe how civic skills are strengthened through Citizenship Education in fostering student participation as citizens. This research is a mix method research with data collection by observation, interviews, and documentation, as well as distributing questionnaires. Participants in this study on qualitative data were lecturers and for quantitative data were 53 students who contracted Civics Learning courses in elementary schools in the Elementary School Teacher Education study program at Esa Unggul University. The results of this study indicate that lecturers provide strengthening of civics skills in Civics Learning courses in Elementary Schools through a project-based learning model, then open space at each meeting for students to be active in the learning process. The results of the analysis of quantitative data, strengthening civic skills through Citizenship Education in fostering student participation as citizens is successful. This can be seen from the survey with the results of Interacting with citizens of other countries to promote personal and shared interests with Agree totaling 91 points; Monitor public events and issues with Agree totaling 123 points; Deliberate and make decisions on public policy issues with Agreed totaling 108 points; Influencing policy decisions on public issues with Agree totaling 100 points; Carry out policy decisions on public issues with Agree totaling 113 points; Taking action to improve political and social life with Agree totals 97 points